Agenesis of Isthmus of the Thyroid Gland in a Patient with Graves-Basedow Disease and a Solitary Nodule. (25th December 2012) - Ozkan, Omer Faruk; Asık, Mehmet; Toman, Huseyin; Ozkul, Faruk; Cıkman, Oztekin; Karaayvaz, Muammer
Abstract : The thyroid is a vascular endocrine gland with two lateral lobes connected by a narrow, median isthmus. Although a wide range of congenital anomalies of the thyroid gland has been reported in the literature, agenesis of the thyroid isthmus is a very rare congenital anomaly. Thyroid isthmus agenesis does not manifest clinical symptoms, and it can be confused with other thyroid pathologies. We describe a patient with no isthmus of the thyroid, associated with Graves-Basedow disease. Thyroid isthmus agenesis should be kept in mind in order for surgical procedures involving thyroid pathologies to be carried out safely.